The analysis of content question words in Embosi and Teke - Ibara, Yvon P. (Journal for Studies in Humanities and Social Sciences, 2015)
This paper demonstrates that the typological classification does not affect all the linguistic descriptive apparatus of languages belonging to the same language family. It appears that the content question word ‘what’ has two distinct positions in Embosi and Teke. In the former, it is a post verbal word, whereas in the latter it is a pre-verbal word; hence challenging Split CP Hypothesis that is unable to explain its occurrence in the languages under discussion.